NUMBER AND STRUCTURE OF MEDICAL STAFF IN THE SIBERIAN CITIES IN THE GREAT PATRIOTIC WAR OF 1941-1945 - Yuliya A. Davidova (Статистика и экономика)
A dynamics of the number of medical personnel Siberian cities in the Great Patriotic war is analyzed in the article. The author studies quantity and structure of senior and low-grade medical personnel of healthcare institutions, shows its impact on medical and sanitarian anti-epidemic work, as well as considers methods of decision of personnel problem in the region. The study is based on analysis of documents of the State Archive of the Russian Federation, the Russian State Archive of Socio-Political History, the Russian State Archive of Economy and the Regional Archives of the Siberian cities.